An omental fibroma resembling a testicular tumour but presented as an irreducible inguinal hernia - Khoo, Phong Jhiew (J Surg Case Rep, 2017)
We present a case of omental fibroma, which posed a surgical diagnostic dilemma. Primary tumours of the omentum are uncommon, and omental fibromas account for 2% of these. The rarity of omental fibroma and paucity of available information hamper an accurate diagnosis. In this particular case, the diagnostic process was misleading. The history was classical of an irreducible inguinal hernia, but the physical examination and imaging studies were suggestive of a testicular tumour. However, intraoperatively, an omental tumour and a normal testicle were found in the scrotum. Histopathological examination proved the tumour to be a fibroma. The presentation of an omental fibroma in an inguinal hernia sac had never been reported in literature. Due to the rarity of such cases, a thorough history, detailed examination, and objective investigation are the pillars to attain the correct diagnosis.